2018
DOI: 10.12968/live.2018.23.3.102
|View full text |Cite
|
Sign up to set email alerts
|

Lungworm in cattle: treatment and control

Abstract: Treatment options for clinical parasitic bronchitis (PB) are largely based on anthelmintics, with supportive therapy including non-steroidal anti-inflammatories (NSAIDs) and antibiotics, when indicated. Macrocyclic lactones (MLs), benzimidazoles and levamisole are all effective against adult and larval lungworms, so the choice of product depends on other criteria, including duration of action and ease of administration, which can be important in dyspnoeic animals. Control of PB in youngstock can be accomplishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Therefore, the larvae that were recovered on day 15 post‐treatment were well within this period of activity. The expected speed of action of MLs against D. viviparus in order to eliminate adult worms from the lungs is estimated to be ∼24 hours, 15 so the presence of larvae indicates the presence of patent adults. With a pre‐patent period of 21‒28 days, the females producing these larvae must have been present at some early developmental stage during the time of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the larvae that were recovered on day 15 post‐treatment were well within this period of activity. The expected speed of action of MLs against D. viviparus in order to eliminate adult worms from the lungs is estimated to be ∼24 hours, 15 so the presence of larvae indicates the presence of patent adults. With a pre‐patent period of 21‒28 days, the females producing these larvae must have been present at some early developmental stage during the time of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The modern-broad spectrum benzimidazole, imidazothiazole and macrocyclic lactone anthelmintic drugs are effective against L 4 and adult stages of Dictyocaulus spp. in sheep and cattle [91]. In most countries, these drugs are not licensed for use in goats.…”
Section: Discussionmentioning
confidence: 99%
“…Drugs with efficacies less than 100%, can still be useful for lungworm control, but their use risks selection for anthelmintic resistance. Poor efficacy against certain parasite species may be due to inherent pharmacological properties of the drugs, which may be stage specific, for example differing between adults and migrating stages in the lymphatics [91].…”
Section: Discussionmentioning
confidence: 99%
“…A literature search was conducted for information regarding expected speed of action of eprinomectin. While the speed of action of macrocyclic lactones against D viviparus has not been specifically measured, it has been estimated at approximately 24 hours 4 . Another study conducted in 1994 5 showed the speed of action to be similar to that of the benzimidazoles at 36 hours 6…”
mentioning
confidence: 99%